LASER HARDENING OF STEEL C45 - Teirumnieks, Normunds; Grabusts, Peteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The aim of the work is to analyze possibility to replace induction hardening process with laserhardening process in production. In metalworking production to harden the parts of steel C45 is used induction hardening method for the moment. In this work will be used experiments to show the possibility to perform laserhardening with CO2 laser and results should show how good the results gives laserhardening to fulfil the requirements of hardening.